A systematic study of the valence electronic structure of cyclo(Gly–Phe), cyclo(Trp–Tyr) and cyclo(Trp–Trp) dipeptides in the gas phase. Issue 47 (24th November 2021) - Molteni, Elena; Mattioli, Giuseppe; Alippi, Paola; Avaldi, Lorenzo; Bolognesi, Paola; Carlini, Laura; Vismarra, Federico; Wu, Yingxuan; Varillas, Rocio Borrego; Nisoli, Mauro; Singh, Manjot; Valadan, Mohammadhassan; et al.
Abstract : The electronic energy levels of cyclo(glycine–phenylalanine), cyclo(tryptophan–tyrosine) and cyclo(tryptophan–tryptophan) dipeptides are investigated with a joint experimental and theoretical approach. Abstract : The electronic energy levels of cyclo(glycine–phenylalanine), cyclo(tryptophan–tyrosine) and cyclo(tryptophan–tryptophan) dipeptides are investigated with a joint experimental and theoretical approach. Experimentally, valence photoelectron spectra in the gas phase are measured using VUV radiation. Theoretically, we first obtain low-energy conformers through an automated conformer–rotamer ensemble sampling scheme based on tight-binding simulations. Then, different first principles computational schemes are considered to simulate the spectra: Hartree–Fock (HF), density functional theory (DFT) within the B3LYP approximation, the quasi-particle GW correction, and the quantum-chemistry CCSD method. Theory allows assignment of the main features of the spectra. A discussion on the role of electronic correlation is provided, by comparing computationally cheaper DFT scheme (and GW) results with the accurate CCSD method.